Kidney transplantation in Icelandic patients, 2000–2019: are outcomes affected by low volume? - Palsson, Thordur P.; Andresdottir, Margret B.; Jonsson, Eirikur; Jonsson, Johann; Hilmarsson, Rafn; Indridason, Olafur S.; Palsson, Runolfur (Frontiers in Transplantation, 2024)
Background In Iceland, a small number of kidney transplants from living donors (LDs) are performed at Landspitali University Hospital (LUH) in Reykjavik, while deceased donor transplants have until recently invariably been carried out abroad. In this study, we evaluated the outcome of kidney transplantation in Icelandic patients. Methods This was a retrospective study that included all Icelandic residents who underwent kidney transplantation between 1 January 2000 and 31 December 2019. Data were obtained from the Icelandic End-Stage Kidney Disease Registry, medical records at LUH, and the Scandiatransplant database. The Chronic Kidney Disease Epidemiology Collaboration equation was used to calculate estimated glomerular filtration rate from serum creatinine for recipients and donors aged >18 years, and the modified Schwartz equation for those aged ≤18 years. Survival was estimated using the Kaplan–Meier method, and the log-rank test was employed for group comparisons. Results A total of 229 kidney transplants in 221 patients were performed during the 20-year period, of which 135 (58.9%) were from LDs. Transplants carried out at LUH were 118 (51.5%), of which 116 were from LDs. During a median follow-up of 7.4 years (range 0.1–20), 27 (12.2%) patients died, 20 (74%) of whom had a functioning graft. One-year patient survival was 99.1% [95% confidence interval (CI), 97.9–100], 5-year survival was 95.7% (95% CI, 92.7–98.7), and 10-year survival was 87.7% (95% CI, 82.4–93.4). Death-censored graft survival was 98.3% (95% CI, 96.6–100), 96.8% (95% CI, 94.4–99.2), and 89.2% (95% CI, 84.1–94.7) at 1, 5, and 10 years, respectively. Conclusions Patient and graft survival are comparable with those of large transplant centers, demonstrating the feasibility of running a quality kidney transplant program in a small nation in collaboration with a larger center abroad.